1990
DOI: 10.2165/00003088-199019030-00006
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Neuromuscular Blocking Effects of Atracurium Besylate and Two of Its Metabolites in Patients with Normal and Impaired Renal Function

Abstract: The pharmacokinetics of atracurium, laudanosine and the quaternary alcohol were studied in patients with normal and impaired renal function following intravenous administration of atracurium. Anaesthesia consisted of thiopental, fentanyl, halothane and nitrous oxide in oxygen. Plasma and urine concentrations of the parent compound and its degradation products were measured by high performance liquid chromatography. Renal failure was defined as a creatinine clearance of less than 5 ml/min; it caused no signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

1992
1992
2000
2000

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…The t' 12!3 of the monoquaternary alcohol is similar to that of the parent compound (27 min), but, unlike atracurium, it is significantly longer in patients with renal failure (Vandenbrom et al 1990). The accumulated pharmacokinetic knowledge of atracurium biotransformation fully justifies using rapidly metabolised drugs for short procedures.…”
Section: Atracuriummentioning
confidence: 86%
See 1 more Smart Citation
“…The t' 12!3 of the monoquaternary alcohol is similar to that of the parent compound (27 min), but, unlike atracurium, it is significantly longer in patients with renal failure (Vandenbrom et al 1990). The accumulated pharmacokinetic knowledge of atracurium biotransformation fully justifies using rapidly metabolised drugs for short procedures.…”
Section: Atracuriummentioning
confidence: 86%
“…Doxacurium ) and pipecuronium (Agoston & Richardson 1985) have a long duration of action comparable with that of pancuronium; however, both appear to be free of cardiovascular side effects. The pharmacokinetics of atracurium (Vandenbrom et al 1990;Ward & Weatherley 1986), vecuronium (Bencini et al 1986a), pipecuronium (Caldwell et al 1989), doxacurium (Dresner et al 1990) and rocuronium (Wierda et al 1991 a) have been reported. There is limited information on the pharmacokinetics of mivacurium (De Bros et al 1987).…”
Section: Standard Nondepolarising Neuromuscular Blocking Agentsmentioning
confidence: 99%
“…Atracurium undergoes spontaneous degradation via Hofman elimination, a non-enzymatic breakdown process occurring at physiological pH and temperature, to produce laudanosine ( Fig. 1) and pentamethylene-1,5 diacrylate [3]. There is also some ester hydrolysis by non-specific plasma esterases.…”
Section: Introductionmentioning
confidence: 99%
“…Das Computertomogramm des Thorax zeigte Infiltrationen im Bereich des rechten Unterlappens sowie eine abszeßverdächtige Verdichtung im Bereich des Mittellappens. Entsprechende Veränderungen fanden sich bei Urämikern [8,19]. Zur antibiotischen Abdeckung erhielt der Patient Cefotiam, Gentamycin und Metronidazol.…”
Section: Introductionunclassified